Assessing fetal movements in pregnancy: A qualitative evidence synthesis of women's views, perspectives and experiences - Valerie Smith; Kathryn Muldoon; Vivienne Brady; Hannah Delaney (BMC, 2021)
Abstract Background Raising awareness of the importance of fetal movements (FMs) and advising women on the appropriate action to take if they experience reduced FMs, is important for minimising or avoiding adverse perinatal outcomes. To gain insight and understanding of women's perspectives of assessing FMs in pregnancy, we conducted a qualitative evidence synthesis. Methods A qualitative evidence synthesis using thematic synthesis was conducted. Studies were eligible if they included pregnant women who were at least 20 weeks gestation and reported qualitative data from women on assessing FMs in pregnancy. MEDLINE, CINAHL, EMBASE, PsycINFO and Social Science Citation Index, from inception to July 2020, were searched. The methodological quality of included studies was assessed by at least two reviewers using an Evidence for Policy and Practice Information (EPPI)-Centre quality assessment tool. Data synthesis, using the Thomas and Harden framework, involved line by line coding of extracted data, establishing descriptive themes, and determining analytical themes. Confidence in the findings was assessed using GRADE CER-Qual. Results Nine studies, involving 2193 women, were included in the review. The methodological quality of the studies was overall generally high. The synthesis revealed three dominant themes, and seven sub-themes that reflected women's perspectives of assessing FMs in pregnancy. These were; 1) How women engage with FMs, with subthemes of informal engagement, formal engagement, and strategies to stimulate FMs; 2) ' ... like a feather inside my belly' - articulating and describing FMs, with sub-themes of sensations associated with FMs and timing and frequency of FMs; and 3) FMs and help/health seeking, with sub-themes of information sources and interacting with healthcare professionals. Confidence in the findings was either high or moderate, although two findings were rated low confidence and one very low. Conclusion This qualitative evidence synthesis reveals that women informally engage with FMs during pregnancy. Women commonly adopt strategies to stimulate FMs when concerned. The use of the internet was a common source of obtaining information regarding FMs. Women require better support when contacting healthcare professionals about FMs. As only three of the nine included studies were exclusively qualitative in design, further qualitative studies exploring women's perspective of assessing FMs in pregnancy are required.